Fabrication of aggregation induced emission active luminescent chitosan nanoparticles via a "one-pot" multicomponent reaction. (5th November 2016) - Wan, Qing; Liu, Meiying; Xu, Dazhuang; Mao, Liucheng; Tian, Jianwen; Huang, Hongye; Gao, Peng; Deng, Fengjie; Zhang, Xiaoyong; Wei, Yen
Highlights: Fabrication of aggregation induced emission active chitosan through a multicomponent reaction. The multicomponent reaction can occur under rather mild experimental conditions.. The WS-Chitosan@An-CHO LPNs are promising for biological imaging applications. The multicomponent reaction can also be utilized for fabrication of many other LPNs. Abstract: Chitosan based nanomaterials have been extensively examined for biomedical applications for their biodegradability, low toxicity, biological activity and low cost. In this work, a novel strategy for fabrication of luminescent polymeric nanoparticles (LPNs) based on aggregation induced emission (AIE) dye and water soluble chitosan (WS-Chitosan) were firstly developed via a highly efficient mercaptoacetic acid (MA) locking imine reaction. In this multicomponent reaction (MCR), MA serves as "lock" to connect 9, 10-Bis(aldehydephenl)anthracene dye (An-CHO) and amino-containing WS-Chitosan under mild reaction conditions. The obtained WS-Chitosan@An-CHO LPNs show strong yellow emission and great water dispersibility. Biological evaluation results demonstrated that synthetic luminescent polymeric nanoparticles possess desirable cytocompatibility and distinct imaging properties. Therefore, we have developed a facile and useful method to fabricate AIE active nanoprobes with desirable properties for various biomedical applications. This strategy should be a general and easy handling tool to fabricate many other AIE dye based materials.